Association Between Antihypertensive Medication Adherence and Visit‐to‐Visit Variability of Blood Pressure. Issue 2 (28th November 2012) - Muntner, Paul; Levitan, Emily B.; Joyce, Cara; Holt, Elizabeth; Mann, Devin; Oparil, Suzanne; Krousel‐Wood, Marie
<x xml:space="preserve">Abstract</x> It has been hypothesized that high visit‐to‐visit variability (VVV) of systolic blood pressure (SBP) may be the result of poor antihypertensive medication adherence. The authors studied this association using data from 1391 individuals taking antihypertensive medication selected from a large managed care organization. The 8‐item Morisky Medication Adherence Scale, administered during 3 annual surveys, captured self‐report adherence, with scores <6, 6 to <8, and 8 representing low, medium. and high adherence, respectively. The mean (standard deviation [SD]) for SD of SBP across study visits was 12.9 (4.4), 13.5 (4.8), and 14.1 (4.5) mm Hg in participants with high, medium, and low self‐reported adherence, respectively. After multivariable adjustment and compared with those with high self‐report adherence, SD of SBP was 0.60 (95% confidence interval, 0.13–1.07) and 1.08 (95% confidence interval, 0.29–1.87) mm Hg higher among participants with medium and low self‐report adherence, respectively. Results were consistent when pharmacy fill was used to define adherence. These data suggest that low antihypertensive medication adherence explains only a small proportion of VVV of SBP. J Clin Hypertens (Greenwich). 2012; 00:00–00. ©2012 Wiley Periodicals, Inc.